Probiotics treatment ameliorated mycophenolic acid-induced colitis by enhancing intestinal barrier function and improving intestinal microbiota dysbiosis in mice - Zhang, Pengpeng; Chen, Jinwen; Ming, Yingzi; Niu, Ying (Frontiers in Microbiology, 2023)
Background: Mycophenolic Acid (MPA) -induced colitis was still a severe side effect and challenge faced by solid transplant recipients. We aimed to explore the function and mechanism of probiotics in the treatment of MPA-induced colitis.: In this study, 15 mice (C57BL/6) were randomly assigned into three groups: control (CNTL) group (n=5), MPA group (n = 5) and the MPA+Probiotic group (n = 5). Bifid Triple Viable capsules, which were drugs for clinical use and consisted of Bifidobacterium longum, Lactobacillus acidophilus, and Enterococcus faecalis, were used in Probiotic group. Body weight change, stool scores, colon histopathology and morphology were used to evaluate the disease severity. The intestinal mucosal barrier function was assessed by measuring the expression level of secretory immunoglobulin A (sIgA), Zonula occludens-1 (ZO-1) and Occludin. Finally, 16S rDNA sequencing and bioinformatics analysis were performed on mice feces to compare the different intestinal microbial composition and diversity among three groups. Results: Compared with the CNTL group, the mice in MPA group showed a significantly decreased body weight, increased stool scores, shortened colon length and severe colon inflammation. However, probiotics treated MPA mice reversed the disease severity, indicating that probiotics ameliorated MPA-induced colitis in mice. Mechanistically, probiotics improved the intestinal barrier function by up-regulating the expression of sIgA, ZO-1 and Occludin. Moreover, MPA-induced colitis led to intestinal microbiota dysbiosis, including the change of Firmicutes/Bacteroidetes ratio, α-and β-diversity. But probiotic treated group showed mild change in these microbial features. Additionally, we found that Clostridiales was the most significantly different microbiota flora in MPA group. Conclusion: Probiotics treatment ameliorated MPA-induced colitis by enhancing intestinal barrier function and improving intestinal microbiota dysbiosis. Clostridiales might be the dominant functional intestinal microflora and serve as the potential therapy target in MPA-induced colitis.